DEA dynamics of chlorine dioxide probed by velocity slice imaging. Issue 26 (14th January 2019) - Gope, Krishnendu; Mason, Nigel; Krishnakumar, E.; Prabhudesai, Vaibhav S.
Abstract : The dissociative electron attachment dynamics of atmospherically important chlorine dioxide (OClO) is unravelled for the first time using velocity slice imaging. Abstract : We report, for the first time, the detailed dynamics of dissociative electron attachment to the atmospherically important chlorine dioxide (OClO) molecule exploring all the product anion channels. Below 2 eV, the production of vibrationally excited OCl − dominates the DEA process whereas at electron energies greater than 2 eV, three-body dissociation is found to result in O − and Cl − production. We find that the internal energy of OCl − and the kinetic energy of Cl − are large enough for them to be relevant in the ozone-depleting catalytic cycle and more investigations on the reaction of these anions with ozone are necessary to completely understand the role of DEA to OClO in ozone depletion. These results also point to an urgent need for comprehensive theoretical calculations of the DEA process to this atmospherically important molecule.